(untitled) (Majalah Kedokteran Bandung, 2019)
Diabetic wound healing problem often occurs if proper care is not given which will lead to the development of a chronic wound. Ageratum (Ageratum conyzoides L.) leaves is one of the most common plants in tropical areas, including Indonesia, which are frequently used in traditional treatment due to its anti-bacterial properties. This experimental study aimed to identify the effects of topical application of Ageratum leaf extract on wound healing based on histopathological examination of the reepithelization, ulceration, neovascularization, and the presence of inflammatory cells. This study was performed in the period of September to December 2017 at the Pharmacology and Pathology Anatomy laboratories of Dr. Hasan Sadikin General Hospital Bandung, Indonesia. Excisions were made on the back of the 36 rats that were divided into control and test groups. The test group then received a topical application of Ageratum leaf extract. The resulting histopathologic appearance of the wound was then examined. The test group showed better wound healing in all parameters inspected when compared to the control group. Mann-Whitney Test with 95% confidence interval (p<0.05) showed that the re-epithelialization, ulceration, neovascularization, and presence of inflammatory cells reflected a statistically significant improvement in the test group (p=0.319, p=0.290, p=0.251, and p=0.245, respectively). This study concludes that the topical application of Ageratum leaf extract has a statistically significant benefit on diabetic wound healing. Pengaruh Histopatologis Ekstrak Daun Ageratum (Ageratum Conyzoides) terhadap Akselerasi Penyembuhan Luka Setelah Luka Eksisi Akut pada Epidermis pada Model 2 Diabetes Mellitus Tikus Sprague Dawley (Rattus norvegicus) Luka diabetes sering menyebabkan luka kronik jika tidak mendapat penanganan yang tepat. Ageratum (Ageratum conyzoides) merupakan tanaman khas daerah tropis termasuk Indonesia, yang daunnya digunakan untuk pengobatan tradisional karena mengandung zat anti bakteri. Penelitian eksperimental ini menggunakan desain kelompok kontrol post-test untuk mengidentifikasi efek aplikasi topical dari ekstrak daun Ageratum pada penyembuhan luka dengan pemeriksaan histopatologis dari reepitelialisasi, ulserasi, neovaskularisasi, dan sel radang. Penelitian ini dilakukan antara September hingga Desember 2017 di laboratorium Farmakologi dan Patologi Anatomi Rumah Sakit Umum Dr. Hasan Sadikin Bandung. Eksisi dilakukan pada tiap-tiap tikus dari 36 tikus yang dibagi menjadi kelompok kontrol dan kelompok uji di mana kelompok uji dilakukan perawatan dengan ekstrak etanol daun ageratum secara topikal. Setelah diaplikasikan ekstrak daun Ageratum, luka diperiksa secara histopatologi. Observasi pada kelompok uji menunjukkan penyembuhan luka eksisional tikus diabetes yang lebih baik daripada kelompok control untuk semua parameter. Uji Mann-Whitney dengan interval kepercayaan 95% (p <0,05) menunjukkan bahwa nilai p untuk reepitelisasi, ulserasi, neovaskularisasi, dan sel radang adalah p=0,319, p=0,290, p=0,251, dan p=0,245. Aplikasi topikal dari ekstrak daun Ageratum memiliki manfaat pada penyembuhan luka diabetes dan hasilnya signifikan secara statistik.